Jointly Catalytic Synthesis of Vinyl Chloride and Chloroprene from Acetylene - A.R. Karjavov., N.I. Fayzullayev., N.X. Musulmonov (International Journal of Control and Automation, 2020)
As a result of studying the influence of the mass transfer coefficient (transportation) on the process productivity and the influence of other factors, the technological parameters of the catalytic flocculant of vinyl chloride and the chloroprene extraction reactor of acetylene were calculated and the main indicators of the compatibility of technological capabilities of environmental and economic factors were substantiated.The process of co-production of vinyl chloride and chloroprene by hydrochlorination of acetylene in the liquid phase was also studied. Process parameters are found that provide vinyl chloride and chloroprene with high selectivity and acetylene conversion. Some kinetic laws of acetylene hydrochlorination were also studied.As a result of the studies, a technological scheme of the combined receipt of vinyl chloride and chloroprene was created, and the material balance of the process was calculated.